Risk of falls and fear of falling in older adults residing in public housing in Ontario, Canada - Pirrie, Melissa; Saini, Guneet; Angeles, Ric; Marzanek, Francine; Parascandalo, Jenna; Agarwal, Gina (My University, 2021)
Falls in older adults is a widely researched topic. However, older adults residing in public housing are a vulnerable population that may have unique risk factors for falls. This study aims to describe the prevalence and risk factors for falls, fear of falling, and seeking medical attending for falls in this population.
An infographic describing the results from the following study published in BMC Geriatrics: "Risk of falls and fear of falling in older adults residing in public housing in Ontario, Canada: findings from a multisite observational study".